PENGARUH GOOD CORPORATE GOVERNANCE DAN VOLUNTARY DISCLOSURE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DI INDONESIA - Kezia Stefany; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
In this changing of the present day which is changed according to the emerging age, Good Corporate Governance already became an important element and also the inseparable part of the institution or the company’s activities continuity. Good Corporate Governance has the purpose to monitor the activities which runs inside the company or organization and keeping the integrity on achieving the goal of the organization. While the Voluntary Disclosure is the inquiries or sharing of information that is given voluntarily by the company outside the mandatory disclosure, especially mentioned in this study are the financial information and the company’s operational activity. In this study, it is studied about how GCG could have an effect to the company’s financial performance, how the company did the financial controlling by using the principles of GCG, and does the Voluntary Disclosure have any effect to the company’s financial performance. Therefore this study is done with the purpose to examine if the Good Corporate Governance and Voluntary Disclosure have effects to the company’s financial performance, especially for the manufacturing companies in Indonesia.This study is done by using the quantitative method, and the testing tools used in this study are the descriptive analysis method and the classical assumption test. The classical assumption test inquires the normality test, linearity test, multicolinearity test, autocorrelation test, and heteroscedasticity test. Also there is fit and goodness test that inquires the determination coefficient test, the F-test, and the T-test.Based on the studies that has been done, GCG which is measured by the independent commissioner variable has a positive effect to the organization’s financial performance. While the voluntary disclosure which is measured by the return of equity (ROE) variable does not have an effect to the organization’s financial performance.